Effects of micro- and macro-stressors and resilience factors on the mental health of parents caring for chronically ill and disabled children and adolescents - Jan Broll; Sarah K. Schäfer; Daniel Lüdecke; Stefan Nickel; Klaus Lieb; Isabella Helmreich (BMC Nursing)
Abstract Background This study examines the impact of non-care-related stressors and resilience factors on the mental health of caregivers for chronically ill and disabled children. It aims to identify the daily stressors and protective factors most relevant to caregiver well-being. Methods A total of 202 caregivers (predominantly female, aged 25–59) participated in a survey measuring exposure to daily micro-stressors, such as household tasks and financial pressures, and macro-stressors, such as significant life events. Resilience factors, including social support and internal locus of control, were also assessed. Descriptive statistics and regression analyses explored the relationship between stressors, resilience factors, and psychological distress. Results Micro-stressors were strongly associated with higher levels of psychological distress, underscoring the cumulative burden of frequent, daily stressors. In contrast, macro-stressors had no significant impact on distress, possibly due to their lower frequency or differences in perception. Resilience factors, particularly social support and internal locus of control, buffered against distress, demonstrating their protective role. Internal locus of control moderated the relationship between micro-stressors and distress, indicating that caregivers who felt greater personal control over their circumstances were better able to manage the negative effects of daily stressors. Conclusions The findings highlight the significant toll of daily micro-stressors on caregivers’ mental health and emphasize the important role of resilience factors in mitigating this burden. Strengthening caregivers’ social networks and fostering internal control beliefs could be key components of interventions designed to improve their well-being. These results suggest that supporting caregivers is essential not only to enhance their quality of life but also to sustain their caregiving roles. Further research should investigate the long-term effects of interventions targeting resilience and explore additional protective factors that may buffer against daily stressors in this vulnerable population. These findings have important implications for disability and rehabilitation services aiming to provide holistic caregiver support. Trial registration DRKS00027465, 2022-01-04 (German Clinical Trials Register); NCT05418205, 2022-03-01 (ClinicalTrials.gov).